2012
DOI: 10.1177/0146167211436117
|View full text |Cite
|
Sign up to set email alerts
|

Your Love Lifts Me Higher! The Energizing Quality of Secure Relationships

Abstract: Three studies tested and confirmed the hypothesis that secure attachment relationships lead to feelings of security and energy, as well as willingness to explore. In Study 1, priming a secure attachment relationship increased felt security and energy. In Studies 2 and 3, felt energy mediated the effect of (primed) secure attachment relationships on willingness to explore. In Study 3, the effect of (primed) secure attachment relationships on felt energy and willingness to explore was independent of general posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 44 publications
5
93
1
Order By: Relevance
“…The finding that partner reflection yields eustress responses also fits with research linking happy, secure relationships to psychological energy and desire for exploration (see Luke et al., ). It seems that, when happy, partner reflection triggers physiological outcomes consistent with the idea that romantic partners are secure bases, inspiring people to explore their environment.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The finding that partner reflection yields eustress responses also fits with research linking happy, secure relationships to psychological energy and desire for exploration (see Luke et al., ). It seems that, when happy, partner reflection triggers physiological outcomes consistent with the idea that romantic partners are secure bases, inspiring people to explore their environment.…”
Section: Discussionsupporting
confidence: 79%
“…In particular, we hypothesized that reflecting on relationship elements involving romantic love would trigger bodily stress responses, consistent with prior research (e.g., Loving et al., ). We further predicted that these responses would reflect eustress (stress linked with positive affect) as opposed to distress (stress linked with negative affect), given the established associations between romantic love and positive and euphoric feelings (see Bianchi‐Demicheli et al., ; Kim & Hatfield, ; Luke et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Green and Campbell [34] asked people to read generic sentences describing secure or insecure close relationships and found that a secure prime, compared with an insecure prime, led to greater endorsement of exploration-related behavior and greater liking for novel pictures. Moreover, Luke, Sedikides, and Carnelley [35] found that security priming, as compared with neutral priming, increased both vitality and willingness to learn and that these effects could not be explained by positive effect. Additionally, Mikulincer, Shaver, and Rom [36] found that implicit exposure to the name of a security provider (nominated in the WHOTO) led to better performance on a creative problem-solving task than implicit exposure to the names of others who were not nominated as attachment figures.…”
Section: Enhancing Security In the Laboratorymentioning
confidence: 99%